2008
DOI: 10.1128/jcm.01162-08
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tuberculous Endometritis with Infertility and Other Gynecological Complaints of Women in India

Abstract: Endometrial biopsy samples derived from 393 patients with assorted gynecological complaints were investigated for mycobacterial infection. By employment of four different techniques, mycobacterial pathogens were detected irrespective of the nature/type of clinical complaint. Mycobacterium tuberculosis was the predominant pathogen detected among the samples investigated.Tuberculosis occurs worldwide and causes widespread morbidity and mortality. Pulmonary and extrapulmonary sites are known to be associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 13 publications
1
30
1
Order By: Relevance
“…In few other reports in which mycobacterial cultures were performed, positivity rates were between 10% and 15% of GTB patients diagnosed on clinical and morphological criteria and a positive TB-PCR. [8][9][10][11]29 PCR positive and BACTEC (culture) and smear negative cases could be explained by the fact that even though smear and culture has remained a gold standard in diagnosis of pulmonary TB, the very low sensitivity for diagnosis of paucibacillary disease limits its practical utility in extra-pulmonary TB. [30][31][32][33] Hence the use of PCR is suggested as an alternative test especially in culture-negative GTB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In few other reports in which mycobacterial cultures were performed, positivity rates were between 10% and 15% of GTB patients diagnosed on clinical and morphological criteria and a positive TB-PCR. [8][9][10][11]29 PCR positive and BACTEC (culture) and smear negative cases could be explained by the fact that even though smear and culture has remained a gold standard in diagnosis of pulmonary TB, the very low sensitivity for diagnosis of paucibacillary disease limits its practical utility in extra-pulmonary TB. [30][31][32][33] Hence the use of PCR is suggested as an alternative test especially in culture-negative GTB.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12]24 In India, endometrial TB-PCR is also used as screening method for GTB but it demands more evaluation as it is debatable whether PCR positivity indicates infection or disease of the genital tract. By treating all asymptomatic TB-PCR-positive cases, are patients being over-treated?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, atypical mycobacteria also take the Z-N stain. Besides M.tuberculosis, other species like 8,24 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Today, though it has become much less common, because of improved socioeconomic conditions, it has been suggested that any women with infertility that cannot be attributed to a specific cause should be investigated for tuberculosis. 2 Genital TB is always hard to diagnose, because of the fact that it is a silent invader of the genital tract. The only reliable way of making a diagnosis is by actually culturing the tubercle bacillus from tissue sampled from the genital tract.…”
Section: Introductionmentioning
confidence: 99%